Transit signatures of inhomogeneous clouds on hot Jupiters: insights from microphysical cloud modeling - Powell, D; Louden, T; Kreidberg, L; Zhang, X; Gao, P; Parmentier, V (American Astronomical Society, 2019)
We determine the observability in transmission of inhomogeneous cloud cover on the limbs of hot Jupiters through post-processing a general circulation model to include cloud distributions computed using a cloud microphysics model. We find that both the east and west limbs often form clouds, but that the different properties of these clouds enhance the limb-to-limb differences compared to the clear case. Using the James Webb Space Telescope, it should be possible to detect the presence of cloud inhomogeneities by comparing the shape of the transit light curve at multiple wavelengths because inhomogeneous clouds impart a characteristic, wavelength-dependent signature. This method is statistically robust even with limited wavelength coverage, uncertainty on limb-darkening coefficients, and imprecise transit times. We predict that the short-wavelength slope varies strongly with temperature. The hot limbs of the hottest planets form higher-altitude clouds composed of smaller particles, leading to a strong Rayleigh slope. The near-infrared spectral features of clouds are almost always detectable, even when no spectral slope is visible in the optical. In some of our models a spectral window between 5 and 9 μm can be used to probe through the clouds and detect chemical spectral features. Our cloud particle size distributions are not lognormal and differ from species to species. Using the area- or mass-weighted particle size significantly alters the relative strength of the cloud spectral features compared to using the predicted size distribution. Finally, the cloud content of a given planet is sensitive to a species' desorption energy and contact angle, two parameters that could be constrained experimentally in the future.